PENGARUH FREE CASH FLOW, DEBT MATURITY, DAN KINERJA ESG TERHADAP EFISIENSI INVESTASI PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zafira Firjuan Laiga; Einde Evana; Ratna Septiyanti (STKIP Subang, 2026)
This study aims to examine the effect of Free Cash Flow, Debt Maturity, and Environmental, Social, and Governance (ESG) Performance on Investment Efficiency in energy sector companies listed on the Indonesia Stock Exchange during the 2019-2023 period. This study employs a quantitative approach using secondary data obtained from annual reports and sustainability reports. The sample consists of 32 companies selected through a purposive sampling method, resulting in 160 firm-year observations. Data analysis was conducted using panel data regression with the assistance of EViews software, and the Fixed Effect Model (FEM) was selected as the most appropriate estimation model. The results indicate that Free Cash Flow has a significant positive effect on Investment Efficiency, Debt Maturity has no significant effect on Investment Efficiency, while ESG Performance has a significant positive effect on Investment Efficiency. These findings imply that internal cash flow management and the implementation of sustainability principles play an important role in supporting more efficient investment decisions in energy sector companies in Indonesia.